Transfer of the Philippine species of Hemigraphis Nees to Strobilanthes Blume (Acanthaceae) - Deng, Yunfei (Phytotaxa, 2019)
Fourteen species originally described in the genus Hemigraphis are formally transferred to the genus Strobilanthes, following currently accepted generic delimitation in the family. Thirteen new combinations and one new name are proposed.